Geometric invariants of cuspidal edges - Martins, Luciana De Fátima [UNESP]; Saji, Kentaro (Canadian Mathematical Society, 2016)
We give a normal form of the cuspidal edge that uses only diffeomorphisms on the source and isometries on the target. Using this normal form, we study differential geometric invariants of cuspidal edges that determine them up to order three. We also clarify relations between these invariants.
Keywords: Curvature; Cuspidal edge; Wave fronts